Superovulatory response in relation to trace elements (copper, zinc, iron, manganese and cobalt) in embryo donor cattle - VERMA, SHIV KUMAR; JHAMB, DINESH; KUMAR, SURESH; SAXENA, M S (The Indian Journal of Animal Sciences, 2011)
Level of trace elements (serum copper, zinc, iron, manganese and cobalt) was estimated in embryo donor cattle in relation to superovulatory response. Cattle (24) superovulated with FSH-P or PMSG were divided into 3 groups i.e. good, fair and non- responders on the basis of their superovulatory response. The serum level of copper, zinc, iron and manganese were estimated using atomic absorption spectrophotometer. The serum level of copper, zinc, iron and manganese were significantly higher in animals which responded well to gonadotropin treatment compared to nonresponders (1.90±0.04, 2.25±0.04, 4.68±0.06,0.55±0.02 vs 1.35±0.06, 1.69±0.06,3.92±0.12 and 0.27±0.01 μg/ml), respectively. However, the cobalt concentration did not differ significantly between good responders and non-responders (0.63±0.02 vs 0.50±0.03 μg/ml, respectively). The results suggested that serum level of trace elements indicates the health and nutritional status of the animals, which can be used as an indicator for selection of donor animals before including them in an embryo transfer programme.